The Role of Parents in Optimizing Gadgets for Childrens Learning During the COVID-19 Pandemic - Intan Nur Azizah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2021)
The purpose of this research is to respect the legal protection of ethnic Uighur women in Xinjiang, China from the perspective of International Human Rights and to find out and study the resolution of cases of serious international human rights violations against ethnic Uighur women in Xinjiang, China. Legal protection for women of Uighur ethnicity is based on articles 3,4,5,9,10,11, the Universal Declaration of Human Rights, namely by providing protection in the form of protection of the right to life, the rights to freedom, and the right to personal security, and others that are regulated in international legal instruments. 2) Serious human rights violations committed by the government of Xinjiang, China are not justified by international law because they violate the provisions stipulated in the subsequent Universal Declaration of Human Rights for the incidents of human rights violations, so the settlement of disputes between the two parties is carried out by negotiation or mediation. If this method is not effective, the UN Security Council can submit the case to an international court such as the International Criminal Court as regulated in article 1 of the 1998 Rome Statute.